Lessons Learned from the Electoral Experience of the Justice and Development Party (Adalet Ve Kalkinma Parti) 2002-2011 - Nadhera Mohammad Qassem; Nor Hafeza Mohtar; Azhana Mohamad (Journal of Indonesian Social Sciences and Humanities, 2016)
This paper examines the electoral process in Turkey concerning the rise of the Justice Development Party (Adalet Ve Kalkinma Parti or AKP) and their experiences in the Turkish electoral process. The evolution of AKP as a major opposition party until its electoral success is explored. The focal point of this paper is to examine the partys evolution, particularly in the area of changes in strategies, political agenda and responses to external and internal challenges. This study fnds that AKP has managed to win consecutive Turkish elections and has maintained its support from the masses by means of moderate and modern approaches and reforms. This study is based on secondary sources. Books and scholarly articles concerning the issue were examined along with newspaper articles. Furthermore, this paper is purely a descriptive one and not based on any particular theory.